2023
DOI: 10.1038/s41598-023-32992-9
|View full text |Cite
|
Sign up to set email alerts
|

GPX4 is a key ferroptosis biomarker and correlated with immune cell populations and immune checkpoints in childhood sepsis

Abstract: Sepsis is the uncontrolled reaction of the body to infection-induced inflammation, which results in life-threatening multiple-organ dysfunction (MODS). Although the research on sepsis has advanced significantly in recent years, its pathophysiology remains entirely unknown. Ferroptosis is a new-fashioned type of programmed cell death that may have an impact on sepsis development. However, the precise mechanism still needs to be explored. In this paper, Four pediatric sepsis datasets [training datasets (GSE26378… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Ferroptosis plays an active role in regulating immune function in an inflammatory environment 38,39 . In recent years, new views believe that ferroptosis has broad prospects in the occurrence, development, and prevention of sepsis 11,12 . Therefore, the utility of FRGs as potential biomarkers was explored in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferroptosis plays an active role in regulating immune function in an inflammatory environment 38,39 . In recent years, new views believe that ferroptosis has broad prospects in the occurrence, development, and prevention of sepsis 11,12 . Therefore, the utility of FRGs as potential biomarkers was explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 In recent years, new views believe that ferroptosis has broad prospects in the occurrence, development, and prevention of sepsis. 11 , 12 Therefore, the utility of FRGs as potential biomarkers was explored in this study. The analysis results of MEGENA and DFGs were combined to find the characteristic ferroptosis genes in the peripheral blood of septic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPX4, a key enzyme in ferroptosis [59,60], plays a crucial role in averting irondependent toxic lipid ROS formation by converting lipid hydroperoxides to lipid alcohols. The inhibition of GPX4 function induces lipid peroxidation, eventually leading to ferroptosis [61].…”
Section: Key Molecules Governing Ferroptosismentioning
confidence: 99%
“…Maintenance of iron homeostasis is essential for normal cardiac function. Ferroptosis regulates the pathogenesis and progression of many cardiovascular diseases [15,16] and exacerbates fatal sepsis [17]. Qu et al showed that glutathione peroxidase 4 (GPX4), a ferroptosis marker, is associated with immune cell populations in sepsis [18].…”
Section: Introductionmentioning
confidence: 99%